2013
DOI: 10.1080/15567036.2010.504941
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Thermal Energy for Air-conditioning: Case Study of a Green Data Center

Abstract: Solar energy is the source of a temperature difference of about 20 ı C between the surface and ocean layers 1 km deep. This renewable source of energy occurs at 2.5 km off the coast of Mauritius and can be used for air-conditioning in data centers that operate round the clock. The engineering, economic, and environmental implications of using naturally-available cold seawater for cooling of data centers are examined. The energy requirement of cold seawater air conditioning is 94% lower than that for convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Ocean thermal air conditioning can be used to control the air conditioning of buildings by using cold, deep water to cool the fresh water circulating through a building. The cold water must be between 277 K and 284 K. The same technique can also be used in lakes [36,37].…”
Section: Hydroelectric Renewable Energymentioning
confidence: 99%
“…Ocean thermal air conditioning can be used to control the air conditioning of buildings by using cold, deep water to cool the fresh water circulating through a building. The cold water must be between 277 K and 284 K. The same technique can also be used in lakes [36,37].…”
Section: Hydroelectric Renewable Energymentioning
confidence: 99%
“…Some recent studies in numerical modelling of scouring can be found in the works of Bordbar et al (2021), and Bordbar et al (2022a), and Bordbar et al (2022b. Nevertheless, close monitoring will be essential, and whenever required a scour counter-measure method has to be considered (Elahee and Jugoo, 2013). To minimize the environmental impact of pipeline installation for a future onshore WTEBS application (e.g.…”
Section: Onshore Wtebs Constructionmentioning
confidence: 99%
“…The inlet pipelines may intake marine organisms, especially those with low mobility and are smaller than the mesh of the inlet pipe screen, into the system during operation (Avery and Wu, 1994). These organisms will be impinged to the internal walls of the system and will encounter rapid environmental changes, such as temperature, dissolved oxygen, turbidity, and light levels of the water, which to a great extent reduce their chance of survival (Avery and Wu, 1994, Elahee and Jugoo, 2013, Cunningham et al, 2010. This phenomenon has been studied in coastal nuclear power plants and is similar related for WTEBSs (Avery and Wu, 1994, Barnthouse et al, 2019, Chae et al, 2008.…”
Section: Impingement and Entrainment Of Organismsmentioning
confidence: 99%
“…In South America, the "Museum of Tomorrow" (2015) in Rio de Janeiro (Brazil) outstands for its high efficiency chillers and for using seawater from the Guanabara Bay [26]. Meanwhile, deep SWAC has been applied for cooling services in Keahole Point, Honolulu (Hawaii) [27,28,9,12], Nassau (Bahamas) [16], Aruba [9], Port Louis (Mauritius) [29,30,31,17,32], Bora Bora (French Polynesia) [9,3], Tetiatoa Atoll (French Polynesia) [9], Curação [33], Reunion Island (France) [34]. Deep SWAC has also been considered in Montego Bay (Jamaica) [7], Puerto Plata (Dominican Republic) [7] and other Caribbean Islands [7], Florida and California (USA) [35,36,37], Brazilian Coast [38], San Andres (Colombia) [39], Hal Far (Malta) [40], Taitung (Taiwan) [41], Oman [42], Ghana [43] and Qesm Hurghada (Egypt) [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the Caribbean Sea, this is the case of hotels and casinos in Nassau (Bahamas) [16], or Aruba [9] and also Curação [33] projects, the latter aiming to supply cooling to 4 hotels and a power plant through a 0.915 m, 6 km long intake pipeline extending to an intake depth of 850 m. Finally, in the Indian Ocean, the most remarkable projects regard the islands of Mauritius and Reunion. In Port Louis (Mauritius) a SWAC project is being developed [29,30,31,17,32]. That project would replace the traditional air conditioning system, which demands 30 MW of electrical power, with 44 MW of cooling power from cold seawater pumped from 6 km offshore.…”
Section: Introductionmentioning
confidence: 99%